Poem - Price, Margaret (Disability Studies Quarterly, 2008)
Title(s): GlassMargaret Price is assistant professor of writing at Spelman College. Her poetry, articles, and essays have appeared in Breath & Shadow, Wordgathering, College Composition and Communication, Across the Disciplines, and Bitch: Feminist Response to Pop Culture. She is at work on a book about psychosocial disability and academic discourse.